The influence of temperature on the color of TiO2:Cr pigments - Gomes Vieira, Fagner Ticiano; Melo, Danniely Silva; Guedes de Lima, Severino Jackson; Longo, Elson [UNESP]; Paskocimas, Carlos Alberto; Silva Junior, Wilson; de Souza, Antonio Gouveia; Garcia dos Santos, Ieda Maria (Pergamon-Elsevier B.V. Ltd, 2009)
TiO2:Cr brown pigments were prepared via a polymeric precursor derived from the Pechini method. The pigments were analyzed by infrared spectroscopy, X-ray diffraction, ultraviolet-vis spectroscopy, and colorimetry. The increase of the calcination temperature from 700 to 1000 degrees C led to a decrease in the L* values, corresponding to darkening of the pigments. The pigments obtained in this work are darker than those produced by a solid-state reaction method reported before. The change in the pigment color is due to the anatase-rutile phase transition, which leads to a shift in the charge transfer bond (Ti4+ - O2-) due to a change in the crystal field around the chromophore ions. Moreover, the oxidation state of chromium was observed to change, and this also alters the color of the pigments. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Oxides; Chemical synthesis; Crystal structure; Defects; Color centers